2013
DOI: 10.1111/1756-185x.12031
|View full text |Cite
|
Sign up to set email alerts
|

Admission rate and characteristics of hospitalized systemic connective tissue disorders: analysis from a nationwide Thailand healthcare database

Abstract: The admission rate for SCNTD in Thailand was 141 per 100,000 admissions among which SLE was the most common. Overall hospital mortality was 4.1%. Although a lower prevalence was found among systemic vasculitis, it had a higher mortality rate, longer length of stay and greater therapeutic cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge, this study is one of the largest studies describing health care utilization and cost for SJS/TEN management. Previous studies[ 8 11 12 ] have been conducted in less than 50 patients while this study was undertaken in more than 150 patients. The results in this study showed crucial information to health policymakers so as to allocate health care resources to manage SJS/TEN at the population level efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this study is one of the largest studies describing health care utilization and cost for SJS/TEN management. Previous studies[ 8 11 12 ] have been conducted in less than 50 patients while this study was undertaken in more than 150 patients. The results in this study showed crucial information to health policymakers so as to allocate health care resources to manage SJS/TEN at the population level efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…There was another Thai study reporting the average LOS of patients with SJS to be 5.3 days. [ 11 ] Even though the study used a national database from the National Health Security Office, only 15 patients with SJS were determined. Thus, the average LOS from the study might be inaccurate and imprecise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between sexes has been proven by previous studies on most rheumatic diseases. In most rheumatic diseases like PMR, GCA, scleroderma, SLE, etc., female gender was a predisposing factor; one exception is gout, which was more prevalent in men [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the prevalence of polymyositis and dermatomyositis was determined on the basis of population-based administrative data obtained from the Quebec (Canada) physician billing and hospitalization databases [14]. Data obtained from the 2010 national database of the hospitalized patients of the Thai Health Coding Centre were used to establish the admission rate, disease determination, hospital mortality rate, length of hospital stay and hospital charges among patients diagnosed with systemic connective tissue disorders [15]. In another study, data on patients hospitalized with rheumatic diseases in California was abstracted from the state hospitalization database [16].…”
Section: Introductionmentioning
confidence: 99%